Management of Immunization in Public Health Center Related to The Universal Child Immunization (UCI) in Arjowinangun Health Center, Malang - Wiqodatul Ummah; Al Munawir; Farida Wahyu Ningtyias (Humanistic Network for Science and Technology (HNST), 2018)
Malang as a child-friendly city is expected to give a big contribution in the achievement of complete basic immunization so that the number of the incident of diseases that can be prevented by immunization (PD3I) decreased. The decline in the achievement of Universal Child Immunization program in Malang has an impact on the increase of the number of PD3I cases. One of the decreases in the achievement of UCI in Arjowinangun public health center Malang reaching the lowest UCI target due to immunization officer who does not get the immunization technical training, the late reporting of officers from the public health center to the Health Office so that the handling of cases in the field is also too late and the spread of disease is widespread. The purpose of this study is to analyze the management of Immunization Implementation at Arjowinangun Public health centerof Malang City. The type of this research is qualitative research conducted with in-depth interviews, observation and documentation with the number of informants as 14 informants consisting of Surveillance and Immunization Section Head, Head of Arjowinangun Public health center, immunization programmer, midwife and nurse and cadre. The result of this study is that immunization officers have never attended immunization technical training, immunization program planning has been done that is determining target number, determining coverage target, calculating vaccine requirement, and calculating need of syringe, safety box and cold chain. However, there are still deficiencies, which are the high number of target owned by the Central Bureau of Statistics (BPS) with the number of real babies in the field. Immunization program implementation has not fully implemented in accordance with Immunization Implementation Guidance because it does not do counseling to baby's parents before immunization is done, the delay of reporting immunization achievement result from programmer to health service, and has never made official report of waste handling. Monitoring and evaluation has been done by Public health center Arjowinangun. Immunization management at Arjowinangun Public Health Center is still not perfect. Keyword: Management, Immunization, Universal Child Immunization